Configuration and optimization of migration planning in global production networks. (November 2021) - Moser, Emanuel; Verhaelen, Bastian; Haefner, Benjamin; Lanza, Gisela
Abstract: Uncoordinated decisions in production networks lead to inefficient structures that endanger a company's competitiveness. To stay competitive in the future, manufacturing companies must focus their production and migrate their production network into agile structures. This paper presents a methodology for migration planning of production networks. First, strategic priorities and capabilities for the production network are formulated. To develop these priorities and capabilities, production resources are identified and combined to desired network configurations. Second, these configurations are transferred into a stochastic- dynamic optimization model to identify a cost-optimal migration strategy. The approach has been validated in the automation industry.